2021
DOI: 10.3390/s21238097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospital-Based and Home-Based Obstructive Sleep Apnoea Severity Measurements with a Single-Lead Electrocardiogram Patch

Abstract: Obstructive sleep apnoea (OSA) is a global health concern, and polysomnography (PSG) is the gold standard for assessing OSA severity. However, the sleep parameters of home-based and in-laboratory PSG vary because of environmental factors, and the magnitude of these discrepancies remains unclear. We enrolled 125 Taiwanese patients who underwent PSG while wearing a single-lead electrocardiogram patch (RootiRx). After the PSG, all participants were instructed to continue wearing the RootiRx over three subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Second, sleep data for the nonsupine position were absent for 14 patients. That is, the chance of sleeping in the nonsupine position at home is higher than that in the hospital because patient felt more comfortable at home 37,38 . Third, we only performed head rotation to the left side in DISE because the examiner was standing on the left side of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, sleep data for the nonsupine position were absent for 14 patients. That is, the chance of sleeping in the nonsupine position at home is higher than that in the hospital because patient felt more comfortable at home 37,38 . Third, we only performed head rotation to the left side in DISE because the examiner was standing on the left side of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the chance of sleeping in the nonsupine position at home is higher than that in the hospital because patient felt more comfortable at home. 37,38 Third, we only performed head rotation to the left side in DISE because the examiner was standing on the left side of the patients. Safiruddin et al 17 reported that there is no significant difference in DISE with left versus right rotation of the head.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been due to patients were forced to sleep in supine position during PSG examinations conducted at a facility. 32 Also, the absence of EEG in type 3 PM to detect arousals that form part of the hypopnea definitions may underestimate the AHI value. In addition, the total sleep period was estimated from the total recording period, which commenced from switching the light off to switching it on.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been studies in which single-lead ECG patches were worn for 3 days by homebound dementia patients to check for the presence of sleep apnea, but the sleep data from those studies were not used for care. 12 Thus, few efforts are being made to use long-term sleep monitoring data for care. In our previous study, we used a nonwearable device to record the sleep disturbance data of AD patients 3 and found that the sleep states of individual patients could be continuously recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been studies in which single-lead ECG patches were worn for 3 days by homebound dementia patients to check for the presence of sleep apnea, but the sleep data from those studies were not used for care. 12 …”
Section: Introductionmentioning
confidence: 99%